Emperor penguins, what does their future hold?: a first step into the distribution modelling of the species - Edmunds, Ross (2020)
Emperor penguins are an extremely unique and fragile species, living in one of the most desolate biomes on the planet. Unfortunately, the ever-escalating process of climate change sees environments around the globe transform. Antarctica is one of the most fragile regions on the planet and one that has been highlighted to be dramatically affected by climate change. These changes to the environment emperor penguins call home will undoubtedly have impacts on the species, but to this day it is still uncertain as to how much and what kind of an impact this will have. With the unique beauty of this bird species observed nowhere else globally, it is key to strive to fully understand them and attempt to conserve their majestic elegance. Used extensively and prosperously by other ecological modellers due to its countless benefits, a Species distribution models (SDM’s) was developed to analyse and project the range shift of emperor penguins under different future climate scenarios. Utilising quantitative secondary data for current emperor colony occurrence and a variety of environmental variables of a high spatial resolution, a series of scenarios were run through Maxent. With the models success in predicting emperor colony occurrence in the current environment to a high degree of accuracy (AUC: 0.973), it was proposed that: Scenario 1 (the Antarctic environment in 2050 under RCP 4.5) was projected to have a slight increase in the total area of predicted presence uniformly around Antarctica and scenario 2 (complete loss of sea ice under current environmental conditions) determined emperors would have a slightly increased environmental range. Results of the SDM concluded that looking to the future under all environmental scenarios would see an overall increase in the predicted presence of emperor penguins. These results contradict much of academic literature, thus it is key to fully understand the limitations of their conclusions. Across all scenarios, the models are predicting an increase in the species environmental niche, but due to the lack of biotic variables, such as food availability, the model cannot accurately depict the species. In addition to this, the physiology and dispersal ability of the species is disputed, suggesting they may not be able to follow the projected niche of the model. Ultimately the limitations of the study restrict its representativeness to the species, thus the results should be interpreted with this in mind. The work highlights areas that need to be developed, allowing for the acquisition of more reflective results. Firstly, the development and utilisation of an advanced aerial surveying capability (RPAS) to allow for more data collection, combined with the application of more climate models to be run for the region of Antarctica; something that is lacking and hinders future distribution modelling on the peninsula. In addition to this the GPS tracking of large proportions of individuals, giving a better understanding of the dynamics of the bird’s life and proving or disproving the results of studies such as this. The model itself (Maxent) was not tailored specifically for the study species, therefore a bespoke model needs to be developed just focus solely on Emperor Penguins, to better reflect the species and its unique environment.